Advances in agronomy. - Sparks, Donald L. (Academic Press, 2016)
Advances in Agronomy continues to be recognized as a leading reference and a first-rate source for the latest research in agronomy. Each volume contains an eclectic group of reviews by leading scientists throughout the world. As always, the subjects covered are varied and exemplary of the myriad of subject matter dealt with by this long-running serial.